The Considerations of Administrative Court Judges on Land Ownership Rights (A Study of Decision No. 8/G/2025/PTUN.BL) - Baharudin, Baharudin; Satria, Valentino Oscar (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the considerations of the judges at the Administrative Court of Bandar Lampung in protecting land ownership rights in relation to the issuance of the Usage Rights Certificate (SHP), as reflected in Decision No. 8/G/2025/PTUN.BL. The dispute arose from the issuance of the SHP in the name of the Mesuji Regency Government on land that had been controlled and claimed as the property of the community without following the proper procedure for the release of rights and the resolution of valid civil legal relations with the plaintiff. This research uses a normative legal method with an empirical legal approach. The issues discussed in this study include the factors underlying the submission of property disputes to the administrative court and how the judge's reasoning is applied when reviewing the validity of the issuance of the usage rights certificate to protect the plaintiff's ownership rights. The findings show that the lawsuit was filed due to the local government's control of land without a clear resolution of civil rights, accompanied by the issuance of an SHP that was suspected to contain administrative defects. In its consideration, the administrative court judges concluded that the court's authority is limited to testing the legality of administrative decisions, not determining civil property rights. The judges emphasized the importance of applying the principles of caution, legal certainty, and the protection of citizens' rights in every action of land administration officials. The decision is deemed appropriate because it maintains a balance between public interest and the protection of public ownership rights, without exceeding the authority of the administrative court. Furthermore, this study emphasizes that certificates, as a product of state administration, cannot be viewed solely as absolute proof, but can still be tested if the issuance process involves procedural violations or the disregard of another party's civil rights.